2009
DOI: 10.1016/j.cortex.2008.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Serial order short-term memory capacities and specific language impairment: No evidence for a causal association

Abstract: This study re-explored the nature of verbal STM deficits in children with specific language impairment (SLI), by distinguishing item and serial order STM processes. Recent studies have shown serial order STM capacity to be a critical determinant of language development, relative to item STM. In Experiment 1, 12 children with SLI, 12 age-matched children and 12 language-matched children were administered serial order recognition and reconstruction tasks. Experiment 2 assessed implicit serial learning abilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
27
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 47 publications
4
27
0
Order By: Relevance
“…Implicit learning of the sequence of pictures of familiar nouns was evident in our Hebb visual-auditory learning task, adding to the growing evidence of Hebbian learning in children (Majerus et al, 2008;Mosse & Jarrold, 2008. Consistent with Mosse and Jarrold (2008), the Hebbian learning pattern observed in our typically developing group was characterized by maintenance of performance on Hebb trials and by a decrement on filler trials.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Implicit learning of the sequence of pictures of familiar nouns was evident in our Hebb visual-auditory learning task, adding to the growing evidence of Hebbian learning in children (Majerus et al, 2008;Mosse & Jarrold, 2008. Consistent with Mosse and Jarrold (2008), the Hebbian learning pattern observed in our typically developing group was characterized by maintenance of performance on Hebb trials and by a decrement on filler trials.…”
Section: Discussionsupporting
confidence: 59%
“…Mosse and Jarrold (2008) suggested that the filler-list decrement was likely due to fatigue effects or to the buildup of proactive interference in their young participants, effects that were counteracted by Hebbian learning on the repeated lists. No group differences in Hebbian learning, when compared to typically developing matched controls, have been found for SLI (Majerus et al, 2008) or Down syndrome (Mosse & Jarrold, 2010) groups. These findings have been interpreted as suggesting that basic serial-order detection and learning mechanisms are preserved in both SLI and Down syndrome, despite deficits in phonological short-term memory in these groups.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…At the end of each trial, the participants were given cards on which the digits presented during the sequence were printed and they had to sort the cards according to their order of presentation. On the digit serial order recognition task (see details in Majerus et al, 2009), participants had to judge whether or not two lists of digits (length 3 to 8), presented auditorily, were presented in the same order. On both tasks, the stimuli were known in advance-the participants were told which items would be presented on each trial, and on the digit serial order reconstruction, the digits were also provided at recall.…”
Section: Discussionmentioning
confidence: 99%